PEMETAAN PERKIRAAN POTENSI GELOMBANG LAUT SEBAGAI PEMBANGKIT LISTRIK TENAGA GELOMBANG LAUT DENGAN SISTEM PELAMIS DI PERAIRAN NIAS - Muhammad Fikry Syach; Muhammad Farras Ayasy; Novia Safinatunnajah (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Meteorologi Klimatologi dan Geofisika, 2020)
The need for electricity using alternative energy is very necessary to replace fossil energy, notably coal power plant sector which is very polluting the environment, the development of alternative energy also supports the realization of sustainable development goals (SDGs) in providing clean and renewable energy. Indonesia has great potential in developing ocean wave energy of around 41 gigawatts, so that it can help to fullfil national electricity consumption. The purpose of this study is to determine the ocean wave potential using conversion of power density of Pelamis (Sea Dragon) electricity analysis in Nias Waters, North Sumatera. This study uses quantitive-case method. This study uses surface wind data from ERA5 and ASCAT in 2019; by processing wind data to generate wind roses using WRPlot software, SMB (Sverdrup-Munk-Bretschneider) method to determine wave forecasting and wave equation using IDL programming, as well as the wave energy density equation using mass-Damper-system electrical energy conversion in the Pelamis module. Based on the study, the results of significant wave height and periode are obtained 0.63 meters and 4.05 seconds, with the conversion angle between the Pelamis arms module is 46,85o using Damper spring between 1.00-1.73 meters, with average of ocean wave density is 82,01 kW/m2; maximum kW/m2; minimum 17,32 kW/m2.